(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article gives a preliminary analysis of the value of the linear morpheme in the Kazakh language. In synharmonic languages morpheme is realized only at the level of style, so in the presence of the Kazakh language consonant morphemes, which traditionally celebrated in all textbooks and teaching aids, not really. Further identified and described spelling and pronouncing articulatory-perceptual structure affixes genitive (іlіk septіk). Revealed unnoticed due to the existing spelling rules of labial harmony in the Kazakh language versions of labial affixes. Thus the number of members has grown affixes genitive. In conclusion drawn visual interactive slide model with a complex articulation, perceptual synharmonic descriptions of all options and examples of the literary text. A systematic analysis of the differential between the signs synharmonic hard / soft labial / neogublennymi options affixes.